Defect-rich cobalt-doped MoS2 / NiSe2 heterojunction nano array electrode and preparation method and application thereof
By introducing defectively rich cobalt-doped MoS2/NiSe2 heterojunction nanoarrays into the electrocatalyst, the problems of slow kinetics and high overpotentials in water electrolysis are solved, and high activity and long-term stable electrocatalytic performance are achieved.
Patent Information
- Application Number
- CN202411838020.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
AI Technical Summary
The slow kinetics and high overpotentials of existing electrocatalysts in water electrolysis limit the energy efficiency of hydrogen production by electrolyzing water. In particular, the thermodynamics of anode oxygen evolution reaction (OER) are slow, making it difficult to apply on a large scale.
Defectively rich cobalt-doped MoS2/NiSe2 heterojunction nanoarray electrode is used to improve the activity and stability of the electrocatalyst through atomic doping, defect engineering and nanoheterogeneous interface.
The HER and UOR activity of the electrocatalyst under alkaline conditions is significantly improved, the overpotential of the electrochemical reaction is reduced, the specific surface area and active sites of the electrocatalyst are improved, and the long-term stable electrocatalytic performance is achieved.
Smart Images

Figure CN119660800A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrocatalysis and new energy materials, and specifically relates to a defect-rich cobalt-doped MoS2 / NiSe2 heterojunction nanoarray electrode and a preparation method and application thereof. Background Art
[0002] Hydrogen has the advantages of high energy density, clean, zero pollution, and renewable. It is a promising energy source to replace traditional fossil resources and improve energy efficiency. Hydrogen production by water electrolysis is a feasible and environmentally friendly method for hydrogen production. However, the widespread application of this method is mainly limited by the slow kinetics and high overpotential of the cathode hydrogen evolution reaction (HER) and the anode oxygen evolution reaction (OER), especially the thermodynamically slow OER reaction. This limitation can be solved by oxidizing other more easily oxidizable organic small molecules, such as glucose and urea. Among them, urea has attracted much attention due to its abundance, low price, and non-flammability. Therefore, urea oxidation reaction (UOR) can be used to couple HER to reduce the energy consumption of hydrogen production by water electrolysis. So far, many precious metal materials have been developed for UOR / OER / HER, such as Ru / Ir, Pt and other precious metal materials, but their high cost and scarcity make them unable to be applied on a large scale. Therefore, it is of great significance to design and develop non-precious metal electrocatalysts with high activity and high stability.
[0003] In recent years, transition metal chalcogenides have attracted extensive attention due to their good thermodynamic stability and high intrinsic electrocatalytic activity. For example, the Xu group designed and synthesized a Mott-Schottky heterojunction catalyst composed of NiSe2 and 2H-MoSe2 by hydrothermal method and selenization treatment for UOR-assisted hydrogen production (Applied Catalysis B: Environmental, 2024, 341, 123312). The in-situ growth of NiSe2 / MoSe2 nanoneedle arrays not only promotes mass transfer, but also accelerates bubble release, while exposing more active sites to participate in the reaction. The results show that the Mott-Schottky heterojunction can promote directional electron transport and surface reconstruction, so that NiSe2 / MoSe2 exhibits excellent HER and UOR performance; Zheng's group used a simple three-step hydrothermal process to in-situ cover the Co-doped MoS2 / NiS2 nanosheet array on a carbon cloth substrate (Co-MoS2 / NiS2 / CC), in which the Co-MoS2 nanosheets were layered and integrated with the NiS2 nanosheets. Due to the introduction of Co atoms and a large number of heterogeneous structures, Co-MoS2 / NiS2 / CC has high conductivity and a large number of accessible active sites, which has a good synergistic effect on the electrocatalytic HER performance (Applied Surface Science, 2021, 563, 150385). However, despite the remarkable results achieved in the above studies, transition metal chalcogenides with a single structure are still limited by insufficient active sites and slow reaction kinetics, which seriously affects their application in the field of water electrolysis. Summary of the invention
[0004] In view of the above-mentioned problems, the present invention further enhances the intrinsic activity of the electrocatalyst by using three surface modification methods, namely, atomic doping, defect engineering and nano-heterojunction interface construction, to provide a defect-rich cobalt-doped MoS2 / NiSe2 heterojunction nanoarray electrode. The electrode material in the present invention firstly adopts a hydrothermal reaction to obtain a self-supporting nickel hydroxide nanosheet array, and then the precursor is selenized by a hydrothermal reaction to synthesize nickel selenide nanosheets. This nanosheet is used as a supporting material for the growth of molybdenum disulfide nanosheets, and is soaked in a NaBH4 solution to produce defect sites. The MoS2 / NiSe2 heterojunction nanoarray containing defect sites is doped with cobalt atoms by a hydrothermal reaction, and finally calcined in a tubular furnace under a mixed gas to obtain a self-supporting defect-rich cobalt-doped MoS2 / NiSe2 heterojunction nanoarray electrocatalyst material.
[0005] The technical solution adopted by the present invention is specifically as follows:
[0006] (1) dissolving metal (cobalt, nickel) salt, ammonium fluoride and urea in deionized water to obtain a mixed aqueous solution;
[0007] (2) soaking the substrate material in the mixed solution prepared above, and subjecting it to a hydrothermal reaction at a specific temperature for a certain period of time, washing it after cooling, and drying it to obtain a nickel hydroxide nanosheet precursor;
[0008] (3) dissolving the raw material Se powder and sodium borohydride in deionized water to obtain a clear NaHSe aqueous solution. Soaking the precursor material in step (2) in the NaHSe aqueous solution, performing hydrothermal treatment again, and after cooling, washing and drying, obtaining a nickel selenide nanosheet array electrode;
[0009] (4) placing the electrode described in step (3) in a mixed aqueous solution of a molybdenum salt and a sulfur source, and subjecting it to a hydrothermal reaction at a specific temperature for a certain period of time, and after cooling, washing, and drying, a MoS2 / NiSe2 heterojunction nanoarray electrode can be obtained;
[0010] (5) placing the electrode in step (4) in a NaBH4 solution, soaking it for a certain period of time, washing it several times, and then hydrothermally reacting it in a solution containing a cobalt salt and thiourea. After cooling, washing it, drying it, transferring it to a tube furnace, heating it to a target temperature under a mixed gas and maintaining it for a certain period of time, thereby obtaining a defect-rich cobalt-doped MoS2 / NiSe2 heterojunction nanoarray electrode;
[0011] Wherein, in step (1), the metal salt includes but is not limited to nitrate, chloride and sulfate; the molar concentration is 10-50 mmol L -1 ; The molar ratio of metal salt, ammonium fluoride and urea is (1-6):(6-10):(1-6).
[0012] Wherein, in step (2), the substrate material includes but is not limited to foam nickel, foam copper, nickel mesh, copper mesh, iron mesh, carbon cloth, carbon paper, etc.
[0013] Wherein, in step (2), the hydrothermal reaction temperature is 100-200° C., and the reaction time is 5-24 h.
[0014] Wherein, in step (3), the concentration of the NaHSe aqueous solution is 0.5 to 3 mol L -1 ; The hydrothermal reaction temperature is 100-200°C, and the reaction time is 5-24h.
[0015] Wherein, in step (4), the molybdenum salt includes but is not limited to sodium molybdate, ammonium molybdate, ammonium metamolybdate, molybdenum trioxide, etc.; the sulfur source includes but is not limited to thioacetamide, L-cysteine, thiourea, sodium sulfide, etc.; the molar ratio of the molybdenum salt to thiourea is (1-5):(2-10); the hydrothermal reaction temperature is 100-200°C, and the reaction time is 5-24h.
[0016] Wherein, in step (5), the concentration of the NaBH4 aqueous solution is 0.05 to 1 mol L -1 ; Cobalt salts include but are not limited to cobalt nitrate, cobalt acetate tetrahydrate, cobalt chloride, etc., and the molar ratio of cobalt salt to thiourea is (0.01-0.2):(0.05-0.5); the hydrothermal reaction temperature is 100-200°C, and the reaction time is 5-24h; the mixed gas includes hydrogen-argon mixed gas, hydrogen-nitrogen mixed gas, etc.; the heating rate is 1-20°C min -1 , the target temperature is 300-600℃, and the holding time is 0.5-3h.
[0017] Another aspect of the present invention provides a defect-rich cobalt-doped MoS2 / NiSe2 heterojunction nanoarray electrode prepared by the above-mentioned preparation method, which is used as a bifunctional electrocatalyst for hydrogen evolution reaction and urea reaction.
[0018] The beneficial effects of the present invention compared with the prior art are as follows:
[0019] (1) The self-supporting electrode of the present invention has a large specific surface area, which can effectively expose more active sites and promote the transfer of charges and the rapid transfer of ions / electrons during the electrochemical reaction.
[0020] (2) The formation of heterogeneous interfaces in the material helps to regulate the electronic structure and performance of the catalyst surface. At the same time, the introduction of selenium and sulfur vacancies can not only reconstruct the local electronic structure, but also increase the active sites of the catalyst and improve the electrocatalytic activity of the catalyst.
[0021] (3) The introduction of transition metals into the material helps to increase the active sites of the electrocatalyst and reduce the charge transfer resistance.
[0022] (4) The defect-rich cobalt-doped MoS2 / NiSe2 heterojunction nanoarray electrode described in the present invention has long-term stable HER and UOR activities under alkaline conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention, the drawings related to the embodiments are briefly introduced below.
[0024] Figure 1 The XRD patterns of the samples prepared in Comparative Example 1, Comparative Example 2 and Example 1 are shown.
[0025] Figure 2 The SEM images of the samples prepared in Comparative Example 1, Comparative Example 2 and Example 1 are shown.
[0026] Figure 3HER performance LSV curves of the samples prepared in Comparative Example 1, Comparative Example 2 and Example 1 in N2-saturated 1M KOH electrolyte and UOR performance LSV curves in N2-saturated 1M KOH+0.5M Urea electrolyte. DETAILED DESCRIPTION
[0027] The present invention is described in detail below in conjunction with embodiments, but the embodiments of the present invention are not limited thereto. Obviously, the embodiments described below are only partial embodiments of the present invention. For those skilled in the art, other similar embodiments obtained without creative work all fall within the protection scope of the present invention.
[0028] The nickel foam substrates used in the examples were pretreated as follows: 1×4 cm nickel foam was cleaned in deionized water, acetone, deionized water, hydrochloric acid, and deionized water ultrasonically for 15 min, placed in a 60° C. vacuum drying oven, and dried for 2 h for easy use.
[0029] Comparative Example 1:
[0030] Preparation of MoS2 / NiSe2 / NF electrocatalyst based on NF:
[0031] (1) Weigh 1 mmol Ni(NO3)2·6H2O, 2 mmol NH4F, and 5 mmol (NH2)2CO in a beaker, add 35 mL of deionized water, stir magnetically for 30 min, and ultrasonicate for 10 min.
[0032] (2) The mixed solution prepared above was poured into a 50 mL polytetrafluoroethylene reactor, and the treated nickel foam was placed vertically in a 120° C. forced air drying oven for 6 h. After the sample was cooled, it was washed several times and vacuum dried at 60° C. for 2 h to obtain Ni(OH)2·0.75H2O / NF.
[0033] (3) 30 mL of deionized water was measured and placed in a 50 mL polytetrafluoroethylene reactor. Under the action of N2, 12 mmol of NaBH4 and 4 mmol of Se powder were added in sequence to prepare a NaSeH mixed solution. Ni(OH)2·0.75H2O / NF was then placed vertically in a 120°C forced air drying oven for hydrothermal reaction for 6 h. After the sample was cooled, it was washed and vacuum dried at 60°C for 2 h to obtain Ni 0.85 Se / NF.
[0034] (4) Weigh 0.075mmol Na2MoO4·2H2O and 0.015mmol CS(NH2)2 in a beaker, add 30mL deionized water, and stir magnetically for 30min. Then pour the obtained mixed solution into a 50mL polytetrafluoroethylene reactor and add the treated Ni 0.85 Se / NF was placed vertically in a forced air drying oven at 180°C for hydrothermal reaction for 6 hours. After the sample was cooled, it was washed several times and vacuum dried at 60°C for 2 hours to obtain MoS2 / NiSe2 / NF.
[0035] Comparative Example 2:
[0036] Preparation of D-MoS2 / NiSe2 / NF electrocatalyst based on NF:
[0037] Weigh 3 mmol NaBH4 into a sealed beaker, add 30 mL of deionized water, wait for the solution to become clear, and then soak the MoS2 / NiSe2 / NF prepared above into the solution. After standing for 30 minutes, wash several times until no bubbles appear in the deionized water, and then vacuum dry at 60°C for 2 hours. Then transfer to a tube furnace and heat to 350°C at a rate of 5°C min -1 , kept warm for 30 min in Ar / H2 (5%) atmosphere, and after cooling to room temperature, D-MoS2 / NiSe2 / NF was obtained.
[0038] Embodiment 1:
[0039] Preparation of Co@D-MoS2 / NiSe2 / NF electrocatalyst based on NF:
[0040] The experimental steps of this embodiment are the same as those of Comparative Examples 1 and 2, except that in Comparative Example 2, a single-atom Co doping step is added after soaking in NaBH4 solution and before heat treatment with Ar / H2 (5%). The MoS2 / NiSe2 / NF washed clean after soaking in NaBH4 is placed in a beaker containing 9 mL of isopropanol and 21 mL of deionized water, and then 0.5 mL of Co / thiourea mixed solution (12.7 mg of cobalt acetate tetrahydrate and 9 mg of thiourea are dissolved in 2 mL of deionized water and allowed to stand overnight to form a Co / thiourea mixed solution) is added, magnetically stirred for 30 min, and then ultrasonicated for 10 min. The mixed solution is then poured into a 50 mL polytetrafluoroethylene reactor, placed in a 160°C forced air drying oven, and subjected to hydrothermal reaction for 10 h. After the sample is cooled, it is washed and vacuum dried at 60°C for 2 h. The sample is then transferred to an Ar / H2 (5%) tubular furnace at 350°C at a rate of 5°C min -1 , keep warm for 30 min, and after cooling to room temperature, Co@D-MoS2 / NiSe2 / NF was obtained.
[0041] Figure 1 The XRD patterns of the samples prepared in Comparative Example 1, Comparative Example 2 and Example 1 are shown; in order to determine the structure and composition of the catalyst, Figure 1 As shown, the diffraction peaks are located at 29.73°, 33.43°, 42.60°, 52.94°, 57.60°, 72.24°, 74.21°, 83.86°, and 87.69°, which correspond to the (200), (211), (220), (222), (321), (421), (332), (511), and (432) planes of NiSe2 (JCPDS no. 041-1495), respectively, and the diffraction peaks are located at 28.99°, 32.67°, 33.57°, 35.90°, 49.78°, 58.34°, 68.44°, 72.85°, and 80.23°, which correspond to MoS2 (JCPDS no.037-1492). According to the MoS2 / NiSe2 / NF heterostructure of comparative example 1, it can be observed that some of the diffraction peaks can match the PDF cards of MoS2 and NiSe2. Compared with the diffraction peaks of MoS2 / NiSe2 / NF of comparative example 1, the diffraction peaks of D-MoS2 / NiSe2 / NF of comparative example 2 are significantly broadened, indicating that the particles of the electrocatalyst are smaller, which may be related to the formation of defect sites. However, after the introduction of cobalt element, compared with the diffraction peaks of D-MoS2 / NiSe2 / NF of comparative example 2, the XRD spectrum of Co@D-MoS2 / NiSe2 / NF of embodiment 1 does not show additional new phases, which may be due to the low cobalt loading.
[0042] Figure 2 The SEM images of the samples prepared by Comparative Example 1, Comparative Example 2 and Example 1 are as follows; it can be seen from the figure that the morphology of Comparative Example 1 (a) is mainly composed of fish-scale nanosheets of MoS2 / NiSe2 / NF; the morphology of Comparative Example 2 (b) is mainly composed of rough hollow nanosheets of D-MoS2 / NiSe2 / NF. It can be seen that after immersion in NaBH4 solution and heat treatment with Ar / H2 (5%), the morphology of the fish-scale nanosheets has changed, the nanosheets have gradually become thinner, and tiny holes have begun to appear on the sheets. This structure can expose a large number of active catalytic sites; and the morphology of Co@D-MoS2 / NiSe2 / NF of Example 1 (c) is similar to that of Comparative Example 2 (b), indicating that the introduction of cobalt element has also had a certain impact on the rough hollow nanosheets, making the nanosheets thinner and having more and more obvious holes. This special structure is more conducive to increasing the specific surface area and high conductivity, and is easy to cause electrocatalytic reaction.
[0043] Figure 3The HER performance LSV curves of the samples prepared in Comparative Example 1, Comparative Example 2 and Example 1 in a 1M KOH electrolyte saturated with N2 and the UOR performance LSV curves in a 1M KOH+0.5M Urea electrolyte saturated with N2. It can be seen from the figure that Example 1 has the best HER and UOR performance, and its 100mA cm -2 The corresponding voltages are the smallest, which are 190 mV and 135 mV respectively. This indicates that the introduction of cobalt elements makes the Co@D-MoS2 / NiSe2 / NF sample of Example 1 have high conductivity and a large number of active sites, which has a good synergistic effect on the performance of the electrocatalyst.
[0044] It should be noted that the above embodiments are only for further illustrating the content of the present invention and should not be construed as limiting the present invention. Without departing from the spirit and essence of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention all fall within the scope of the present invention.
Claims
1. A defect-rich cobalt-doped MoS2 / NiSe2 heterojunction nanoarray electrode, characterized in that: The electrode is composed of a self-supporting MoS2 / NiSe2 heterojunction nanoarray.
2. A defect-rich cobalt-doped MoS2 / NiSe2 heterojunction nanoarray electrode, characterized in that: The electrode is doped with cobalt atoms.
3. A defect-rich cobalt-doped MoS2 / NiSe2 heterojunction nanoarray electrode, characterized in that: The electrode is rich in sulfur and selenium vacancy structural defects.
4. A method for preparing a defect-rich cobalt-doped MoS2 / NiSe2 heterojunction nanoarray electrode according to claims 1-3, characterized in that The steps include: S1: dissolving metal nickel salt, ammonium fluoride and urea in deionized water to obtain a mixed aqueous solution; S2: soaking the substrate material in the mixed solution prepared in S1, and subjecting it to a hydrothermal reaction at a specific temperature for a certain period of time, washing it after cooling, and drying it to obtain a nickel hydroxide nanosheet precursor; S3: dissolving raw material Se powder and sodium borohydride in deionized water to obtain a clear NaHSe aqueous solution. Soaking the precursor material described in S2 in the NaHSe aqueous solution, performing hydrothermal treatment again, cooling, washing, and drying to obtain a nickel selenide nanosheet array electrode; S4: placing the electrode described in S3 in a mixed aqueous solution of molybdenum salt and sulfur source, and performing hydrothermal reaction at a specific temperature for a certain period of time, and after cooling, washing and drying, a MoS2 / NiSe2 heterojunction nanoarray electrode can be obtained. S5: placing the electrode described in S4 in a NaBH4 solution, soaking it for a certain period of time, washing it several times, and then hydrothermally reacting it in a solution containing cobalt salt and thiourea. After cooling, washing, drying, and transferring it to a tubular furnace, heating it to the target temperature under a mixed gas and maintaining it for a certain period of time, a defect-rich cobalt-doped MoS2 / NiSe2 heterojunction nanoarray electrode can be obtained.
5. The preparation method according to claim 4, characterized in that: In step S1, the metal nickel salt includes but is not limited to nitrate, chloride and sulfate, and the molar concentration is 10-50 mmol L -1 ; The molar ratio of metal salt, ammonium fluoride and urea is (1-6):(6-10):(1-6).
6. The preparation method according to claim 4, characterized in that: In step S2, the substrate material includes but is not limited to nickel foam, copper foam, nickel mesh, copper mesh, iron mesh, carbon cloth, carbon paper, etc. The hydrothermal reaction temperature is 100-200°C, and the reaction time is 5-24h.
7. The preparation method according to claim 4, characterized in that: In step S3, the concentration of the NaHSe aqueous solution is 0.5 to 3 mol L -1 ; The hydrothermal reaction temperature is 100-200°C, and the reaction time is 5-24h.
8. The preparation method according to claim 4, characterized in that: In step S4, the molybdenum salt includes but is not limited to sodium molybdate, ammonium molybdate, ammonium metamolybdate, molybdenum trioxide, etc.; the sulfur source includes but is not limited to thioacetamide, L-cysteine, thiourea, sodium sulfide, etc.; the molar ratio of the molybdenum salt to the thiourea is (1-5):(2-10); the hydrothermal reaction temperature is 100-200°C, and the reaction time is 5-24h.
9. The preparation method according to claim 4, characterized in that: In step S5, the concentration of the NaBH4 aqueous solution is 0.05 to 1 mol L -1 ; Cobalt salts include but are not limited to cobalt nitrate, cobalt acetate tetrahydrate, cobalt chloride, etc., and the molar ratio of cobalt salt to thiourea is (0.01-0.2):(0.05-0.5); the hydrothermal reaction temperature is 100-200°C, and the reaction time is 5-24h; the mixed gas includes hydrogen-argon mixed gas, hydrogen-nitrogen mixed gas, etc.; the heating rate is 1-20°C min -1 , the target temperature is 300-600℃, and the holding time is 0.5-3h.
10. A defect-rich cobalt-doped MoS2 / NiSe2 heterojunction nanoarray electrode prepared by the preparation method according to any one of claims 4 to 10, and its application in water electrolysis, metal-air battery or sewage treatment.
Citation Information
Patent Citations
Preparation method of cubic-phase cobalt selenide rich in Se defects and application of cubic-phase cobalt selenide in preparation of hydrogen peroxide through electrocatalytic oxygen reduction
CN116081579A
NiSe2 / CoSe / NF nano-material taking basic nickel cobalt carbonate as precursor and preparation method and application of NiSe2 / CoSe / NF nano-material
CN117920279A
MXene-based difunctional electro-catalytic material as well as preparation and application thereof
CN118727041A
Preparation method for foamed nickel-based catalyst for hydrogen production by water electrolysis
WO2021184563A1
Cited By
Negative electrode composite material, preparation method thereof and battery
CN121035161A
Molybdenum disulfide modified lithium-rich manganese-based positive electrode material rich in sulfur vacancies and preparation method thereof
CN121839624A